A New Multilevel Inverter Topology With Reduce Switch Count - Siddique, Marif Daula; Mekhilef, Saad; Shah, Noraisyah Mohamed; Sarwar, Adil; Iqbal, Atif; Memon, Mudasir Ahmed (Institute of Electrical and Electronics Engineers, 2019)
Multilevel inverters are a new family of converters for dc-ac conversion for the medium and high voltage and power applications. In this paper, two new topologies for the staircase output voltage generations have been proposed with a lesser number of switch requirement. The first topology requires three dc voltage sources and ten switches to synthesize 15 levels across the load. The extension of the first topology has been proposed as the second topology, which consists of four dc voltage sources and 12 switches to achieve 25 levels at the output. Both topologies, apart from having lesser switch count, exhibit the merits in terms of reduced voltage stresses across the switches. In addition, a detailed comparative study of both topologies has been presented in this paper to demonstrate the features of the proposed topologies. Several experimental results have been included in this paper to validate the performances of the proposed topologies with different loading condition and dynamic changes in load and modulation indexes. © 2013 IEEE.